PENGARUH KOMUNIKASI INTERNAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN INDUSTRI MEDIA PT. Riau Media Televisi (Rtv) Pekanbaru - Gita Lestari; Kasmirudin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study uses 3 variables of internal communication, work motivation and employee performance. In internal communication variables have 5 dimensions of downward communication, upward communication, horizontal communication, diagonal communication, and informal communication process. In the variable of work motivation have 3 dimension that is motive, expectation, and incentive. In the variable Employee Performance has 3 dimensions of quantity, quality, and timeliness. Objects in this study are employees of PT. Riau Media Television (Rtv) Pekanbaru which amounted to 63 employees. The analysis used in this research is Validity Test, Reliability Test, Simple Linear Regression, Multiple Linear Regression, Determination Test (R2), Individual Significant Test (t test) and Significant Test (F test).The results showed the Influence of Internal Communication And Work Motivation Against Employee Performance. The better Internal Communication that occurs within the organization and employee work motivation in the company is increasing, the better level of Employee Performance in the company. So also with the motivation of work, the more we motivate employees the better the performance of the company. Results Data from the results of further questionnaires processed and tested with statistics through the help of SPSS program. The calculation results are known R Square is the coefficient of determination. And obtained R Square value of 0.350. The meaning is that the contribution of the variable of Internal Communication, Work Motivation to Employee Performance variable is 35.00%.Keywords: Internal Communication, Work Motivation, Employee Performance